Synthesis of rubber seed shell-derived porous activated carbons for promising supercapacitor application - Rustamaji, Heri; Prakoso, Tirto; Devianto, Hary; Widiatmoko, Pramujo; Febriyanto, Pramahadi; Ginting, Simparmin br; Darmansyah, Darmansyah (International Journal of Renewable Energy Development, 2025)
This work investigates synthesizing activated carbon obtained from rubber seed shells utilizing several activating agents (KOH, CaCl2, and ZnCl2) for supercapacitor applications. Activated carbon was produced from a rubber seed shell using hydrothermal carbonization at 275 °C for 60 minutes and a 120-minute activation treatment at 800 °C. Various activating agents pronounced impacted the pore architecture, surface area, crystallinity, and level of graphitization, which collectively determined the electrochemical characteristics of the resulting materials. Incorporating activation agents enhances the specific surface area and influences the extent of graphitization of activated carbon. The specific surface area of activated carbon products ranges from 367 to 735.2 m² g⁻¹. Further investigation through electrochemical analysis, conducted with a carefully engineered two-electrode system, demonstrated a peak electrode capacitance value of 246 F g-1 at 50 mA g-1 for an ACZn-based supercapacitor. Supercapacitor cells’ energy and power densities reached significant levels, measuring 5.47 Wh kg-1 and 246 W kg-1, respectively. The RSS-derived activated carbon-based supercapacitor exhibited remarkable longevity in a 5000-cycle test, with consistent capacitance retention and coulombic efficiency of 100.11% and 100%, respectively. This work presents a sustainable pathway for producing activated carbon electrodes, contributing to the global circular economy and demonstrating considerable industrial potential.